2019
DOI: 10.1038/s41598-019-51969-1
|View full text |Cite
|
Sign up to set email alerts
|

Broad and Efficient Control of Klebsiella Pathogens by Peptidoglycan-Degrading and Pore-Forming Bacteriocins Klebicins

Abstract: Gram-negative bacteria belonging to the genus Klebsiella are important nosocomial pathogens, readily acquiring resistance to all known antibiotics. Bacteriocins, non-antibiotic antibacterial proteins, have been earlier proposed as potential therapeutic agents for control of other Gram-negative species such as Escherichia, Pseudomonas and Salmonella. This study is the first report describing pore-forming and peptidoglycan-degrading bacteriocins klebicins from Klebsiella. We have identified, cloned, expressed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 30 publications
(34 reference statements)
0
31
0
Order By: Relevance
“…As expected, bacteriocins have an outstanding record to kill or reduce pathogens and drug-resistant pathogens during in vitro assessments (Fuchs et al, 2011;Cui et al, 2012;Gabrielsen et al, 2014;Ishibashi et al, 2014;Al Atya et al, 2016;Jiang et al, 2017;Aguilar-Pérez et al, 2018;Ansari et al, 2018;Denkovskienė et al, 2019;Peng et al, 2019;Newstead et al, 2020). Conventionally, bacteriocins display a non-toxic behavior at in vitro assays (Cebrián et al, 2019).…”
Section: Antibacterial Activity Of Bacteriocins In In Vitro Studiesmentioning
confidence: 84%
See 1 more Smart Citation
“…As expected, bacteriocins have an outstanding record to kill or reduce pathogens and drug-resistant pathogens during in vitro assessments (Fuchs et al, 2011;Cui et al, 2012;Gabrielsen et al, 2014;Ishibashi et al, 2014;Al Atya et al, 2016;Jiang et al, 2017;Aguilar-Pérez et al, 2018;Ansari et al, 2018;Denkovskienė et al, 2019;Peng et al, 2019;Newstead et al, 2020). Conventionally, bacteriocins display a non-toxic behavior at in vitro assays (Cebrián et al, 2019).…”
Section: Antibacterial Activity Of Bacteriocins In In Vitro Studiesmentioning
confidence: 84%
“…Pentocin JL-1 has also been demonstrated to have antibacterial activity against Gram-positive and Gram-negative bacteria, particularly MDR S. aureus ( Jiang et al, 2017 ). Other examples, such as the novel entianin, which has activity against MRSA (ATCC 43300) and vancomycin-resistant Enterococcus faecalis (ATCC 51299) strains ( Fuchs et al, 2011 ), and bacteriocins klebicins have been demonstrated to be active against MDR and carbapenem-resistant Klebsiella species ( Denkovskienė et al, 2019 ). Moreover, novel enterocins DD28 and DD93 showed anti-staphylococcal activity in MRSA ( Al Atya et al, 2016 ).…”
Section: Antibacterial Activity Of Bacteriocins In In Vitro Studiesmentioning
confidence: 99%
“…As mentioned above, several orthologs of ColM, which are produced by Pseudomonas spp., Pectobacterium carotovorum , Burkholderia spp. and Klebsiella species, have been identified [ 50 , 51 , 52 , 53 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. These orthologs present a high sequence similarity with the C-terminal domain of ColM ( Figure 9 ) and some of them have been biochemically and/or structurally characterized, as it will be discussed below.…”
Section: The Orthologs Of Colmmentioning
confidence: 99%
“…Different ColM orthologs from genus Pseudomonas spp. have been identified and characterized [ 50 , 62 , 67 , 69 ]. These are PaeM1, PaeM2, PflM and PsyM, that have been found in P. aeruginosa JJ692, P. aeruginosa NCTC10332, P. syringae pv.…”
Section: The Orthologs Of Colmmentioning
confidence: 99%
See 1 more Smart Citation